A Health Information Quality Assessment Tool for Korean Online Newspaper Articles: Development Study - Naae Lee; Seung-Won Oh; Belong Cho; Seung-Kwon Myung; Seung-Sik Hwang; Goo Hyeon Yoon (JMIR Publications, 2021)
BackgroundConcern regarding the reliability and accuracy of the health-related information provided by online newspaper articles has increased. Numerous criteria and items have been proposed and published regarding the quality assessment of online information, but there is no standard quality assessment tool available for online newspapers. ObjectiveThis study aimed to develop the Health Information Quality Assessment Tool (HIQUAL) for online newspaper articles. MethodsWe reviewed previous health information quality assessment tools and related studies and accordingly developed and customized new criteria. The interrater agreement for the new assessment tool was assessed for 3 newspaper articles on different subjects (colorectal cancer, obesity genetic testing, and hypertension diagnostic criteria) using the Fleiss κ and Gwet agreement coefficient. To compare the quality scores generated by each pair of tools, convergent validity was measured using the Kendall τ ranked correlation. ResultsOverall, the HIQUAL for newspaper articles comprised 10 items across 5 domains: reliability, usefulness, understandability, sufficiency, and transparency. The interrater agreement for the article on colorectal cancer was in the moderate to substantial range (Fleiss κ=0.48, SE 0.11; Gwet agreement coefficient=0.74, SE 0.13), while for the article introducing obesity genetic testing it was in the substantial range, with values of 0.63 (SE 0.28) and 0.86 (SE 0.10) for the two measures, respectively. There was relatively low agreement for the article on hypertension diagnostic criteria at 0.20 (SE 0.10) and 0.75 (SE 0.13), respectively. Validity of the correlation assessed with the Kendall τ showed good correlation between tools (HIQUAL vs DISCERN=0.72, HIQUAL vs QUEST [Quality Evaluation Scoring Tool]=0.69). ConclusionsWe developed a new assessment tool to evaluate the quality of health information in online newspaper articles, to help consumers discern accurate sources of health information. The HIQUAL can help increase the accuracy and quality of online health information in Korea.